Increasing Role of Maternal Immune Activation in Neurodevelopmental Disorders - Boulanger-Bertolus, Julie; Pancaro, Carlo; Mashour, George A. (Frontiers in Behavioral Neuroscience, 2018)
The earliest stages of development are critically sensitive to environmental insults. An unfortunately timed stress on the developing brain can have dramatic consequences for the neurodevelopment and future mental health of the individual. In particular, infection of the mother during pregnancy has been correlated with increased risk of psychiatric and neurodevelopmental disorders. Evidence suggests that maternal immune activation, independently from the infection itself, can be responsible for the outcome in the offspring. This recognition has resulted in expanding study designs from epidemiologic correlations to the search for a causal relationship between activation of the maternal immune system and cognitive consequences for the offspring. However, this causality analysis remained limited in humans until recent work that longitudinally linked specific markers of maternal inflammation during pregnancy with alterations of the newborn brain and cognitive development of toddlers. This focused narrative review compares and discusses the results of these recent studies and places them into the broader landscape of maternal immune activation literature. New data point, in particular, to the association between the levels of IL-6 and modifications of the offspring’s salience network and subsequent cognitive impairments. This article further emphasizes the need to carefully control for potential confounders in studying the effects of maternal immune activation on the neonatal brain as well as the under-investigated consequences of intra-partum fever on offspring neurodevelopment.